2021
DOI: 10.3389/fonc.2021.633462
|View full text |Cite
|
Sign up to set email alerts
|

Can Aspirin Use Be Associated With the Risk or Prognosis of Bladder Cancer? A Case-Control Study and Meta-analytic Assessment

Abstract: Aspirin, widely used to prevent cardiovascular disease, had been linked to the incidence of bladder cancer (BCa). Existing studies focusing on Chinese populations are relatively rare, especially for Northeast China. Meanwhile, relevant studies on the effects of aspirin on the occurrence or prognosis of BCa are inconsistent or even controversial. First, in the case control study, logistic regression analysis was used to investigate the association between aspirin intake and risk of BCa including 1121 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The above ndings matched those ofLiao et al, 2021 who that high stage of BC has obviously higher level of TP53 mutation than the lower stage and also consistent with those ofShao et al, 2021 who reported that TP53 mutations were most frequent among BC patients with high tumor grade. The overall analysis provides a strong support to the initial ndings, which further con rmed the potential diagnosis role of TP53 mutation in advanced BC.The occurrence or recurrence of BC is a molecular biological change or process that is effected by occupational factors, non-occupational factors, genomics and proteomics factors(Fan, et al, 2021).The value of TP53 in bladder cancer as a predictive marker of tumor recurrence and treatment selection is still in debate(Sobhani et al, 2021). But the results of our study settled this matter and statistically proved the the clinical value of TP53 in bladder cancer as a predictive marker of both tumor metastasis and recurrence.Analysis of the data using Log Rank Mantel-Cox for tumor recurrence showed a signi cant association between mutation frequency in exons (2 + 3), 4 and tumor recurrence with P = 0.001, 0.008 respectively while no signi cant association was observed in exon 5.…”
mentioning
confidence: 57%
“…The above ndings matched those ofLiao et al, 2021 who that high stage of BC has obviously higher level of TP53 mutation than the lower stage and also consistent with those ofShao et al, 2021 who reported that TP53 mutations were most frequent among BC patients with high tumor grade. The overall analysis provides a strong support to the initial ndings, which further con rmed the potential diagnosis role of TP53 mutation in advanced BC.The occurrence or recurrence of BC is a molecular biological change or process that is effected by occupational factors, non-occupational factors, genomics and proteomics factors(Fan, et al, 2021).The value of TP53 in bladder cancer as a predictive marker of tumor recurrence and treatment selection is still in debate(Sobhani et al, 2021). But the results of our study settled this matter and statistically proved the the clinical value of TP53 in bladder cancer as a predictive marker of both tumor metastasis and recurrence.Analysis of the data using Log Rank Mantel-Cox for tumor recurrence showed a signi cant association between mutation frequency in exons (2 + 3), 4 and tumor recurrence with P = 0.001, 0.008 respectively while no signi cant association was observed in exon 5.…”
mentioning
confidence: 57%
“…CVD treatment and control generally involve a multitude of drugs and related drug-interactions, with a possible effect on cancer incidence. Considering BCa risk, several studies have considered the relationship with aspirin but have demonstrated inconsistent results and overall null associations [ 26 , 27 , 28 ]. Similar results were assessed for any antihypertensive agents or statin use in a population-based case-control study, highlighting the need for additional long-term follow-up prospective research [ 18 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%